Development of Islamic Religious Education Learning Media Based on Audio Visual Fasting Worship Material Forms a Fearful Personal in Junior High School - Andini Masero; Hikmia A.; St. Marwiyah; Arifuddin Arifuddin (State Islamic Institute of Palopo, 2023)
This research was conducted at SMP Negeri 11 Palopo regarding the development of audio-visual based Islamic religious education learning media which was motivated by the lack of use of learning media, especially in grade VIII and media that are often used in the learning process in the form of textbooks and blackboards where students feel bored so that many students do not pay attention when the teacher explains learning. The method that is often used is the lecture method, the media used is still minimal and sometimes teachers use youtube media for the learning process but it is very rarely used. This study aims to: 1) Know the analysis of media needs for audio-visual based Islamic religious education learning. 2) Know the practicality of audio-visual based Islamic religious education learning media. The research used is development research or called R&D (Research and Development). The development model used is ADDIE which consists of five stages including analysis, design, development, implementation and evaluation. The location of this research was conducted at SMP Negeri 11 Palopo located on Jl, Sultan Hasanudin Km 10. From October 18 to December 18. The subject of this study was 9 class VIII students and the object of research was audio-visual based Islamic religious education learning media. Data collection techniques use interviews with teachers and questionnaires to students. While data analysis techniques are descriptive, qualitative and quantitative descriptive. The results of this study stated: 1) The results obtained from the needs analysis of teachers obtained an average score of 100% with the category of very needed and the needs analysis carried out on students from those who answered the question with the answer Yes obtained an average score of 78% with the category mostly needed and answers Not obtained an average score of 22% category a small part needed. 2) The results of implementation in students by providing practicality questionnaires obtained a percentage of 81.11% with very good categories. So it can be concluded that audio-visual based learning media for fasting worship materials to form a pious person is needed in the learning process, especially in grade VIII of SMP Negeri 11 Palopo.